2017
DOI: 10.1016/j.jped.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic play to prepare children for invasive procedures: a systematic review

Abstract: Evidence related to the use of therapeutic play on anxiety and behavior of children undergoing invasive procedures is still questionable. The absence, in most studies, of the creation of a random sequence to assign the subjects to either the control or the experimental group, as well as allocation concealment, are factors that contribute to these questions. Another issue that characterizes an important source of bias is the absence of blinded evaluators. It is necessary to perform further studies that will tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 23 publications
1
42
0
12
Order By: Relevance
“…However, because of the very nature of the intervention, blinding of patients and outcome assessors would have been difficult. Although children are unlikely to change their behaviour even when they know they are participating in a certain intervention, 9 however, lack of blinding may contribute to an importance source of bias because the assessors know the group allocation of children which likely affect their ratings of children’s emotional manifestation during the CR procedures. Nevertheless, different strategies were employed to minimise the potential bias.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because of the very nature of the intervention, blinding of patients and outcome assessors would have been difficult. Although children are unlikely to change their behaviour even when they know they are participating in a certain intervention, 9 however, lack of blinding may contribute to an importance source of bias because the assessors know the group allocation of children which likely affect their ratings of children’s emotional manifestation during the CR procedures. Nevertheless, different strategies were employed to minimise the potential bias.…”
Section: Limitationsmentioning
confidence: 99%
“… 8 A recent systematic review of 14 articles found that therapeutic play was commonly employed for children undergoing invasive procedures, such as elective surgery, vaccination, blood collection or dental treatment in inpatient settings, with positive changes in the behaviour of those who participated in play sessions and a reduction in their anxieties. 9 However, some of these studies were limited by the lack of random assignment of subjects into intervention or control groups. Besides, the efficacy of therapeutic play interventions is yet to be determined, as the studies reported were mainly based on clinical observation and most of the play manuals, which should have set out specific procedures to improve fidelity, were not fully described.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were reported in several studies reporting the outcomes of providing children with pre-operative care in child-friendly environments where children and their PCGs experienced reduced anxiety. Medical procedures often trigger anxiety [63][64][65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…Over-anxiety leads to the children's unwillingness during the medical treatment results in creating negative feelings towards the personnel and preventing effective medical treatment (11). Thus, clinical researchers are required to develop, implement, and evaluate methods to reduce the children's anxiety and their ability to overcome hospitalization and invasive procedures stresses (12). Considering children's age and previous experiences, nurses should make the children ready for the procedure (13).…”
Section: Introductionmentioning
confidence: 99%